THE USE OF INDIGENOUS KNOWLEDGE IN FLOOD DISASTER FORECASTING FOR FLOOD DISASTER RISK REDUCTION IN NORTHERN KATSINA STATE - Abdulrashid, Lawal (FUDMA JOURNAL OF SCIENCES, 2021)
This study investigates the use of indigenous knowledge by the communities of semi-arid areas of Katsina state in forecasting/predicting the risk of flood disaster. Data were collected through semi-structured interviews with purposefully selected respondents and focus group discussions. It was found that indigenous knowledge of disaster monitoring, prediction and early warning is based on the observation of behaviors of animals, birds, insects, shrubs, trees, wind, temperature, and cloud among others. The communities of northern Katsina state faces other natural disaster challenges, flood is among the major disaster risk experienced by the population and over the years they have evolved indigenous ways that helped them not only in predicting this natural disaster but also in devising techniques and mechanism of dealing with it. Documentation of disaster risk reduction information and development of disaster risk reduction policy was recommended to deal with the situation